Síntese, estudo in silico e avaliação da atividade antimicrobiana de análogos e homólogos das riparinas de Aniba riparia (Nees) Mez - Sousa, Gabriela Ribeiro de (2020)
The isolated N-benzoyltyramines of Aniba riparia (Nees) Mez (Lauraceae), known as riparins, make up a class of alkaloids containing an amide group. The riparins named I, II, III and the synthetic analogue riparin IV, present a wide spectrum of biological activity, highlighting the antimicrobial, antidepressant and anxiolytic activity. Due to the rare occurrence in plants and the important pharmacological potential, the synthesis of riparin analogues and derivatives has been of great interest in the academic-scientific environment. Thus, the present work aimed at the synthesis of natural and synthetic riparin analogues and counterparts, as well as the in vitro and in silico evaluation of antimicrobial activity for such substances. The analogues of riparins I, II, III and IV were obtained using the classical Schotten-Baumann method and by aminolysis of esters via DBU with yields of 56-64%. To obtain the nor and dinor homologues, the preparation methods consisted of Schotten-Baumann reaction, ester aminolysis and aminolysis via BOP/pyBOP, obtaining yields of 34 to 70%. Antimicrobial activity of the substances obtained using bacterial strains was performed: S. aureus (ATCC-25923), S. epidermidis (ATCC-12228), E. coli (ATCC-18739), P. aeruginosa (ATCC-9027) and C. albicans (ATCC-60193), C. tropicalis (ATCC-13803) and C. krusei (ATCC-6258). This study revealed that the products tested had activity from strong to moderate, with minimum inhibitory concentration ranging from 64 to 1024 µg/mL. In parallel, the molecular docking study of the substances with the enzymes 14α-lanosteroldimethylase, exo beta-(1,3)-glucanase, N-Myristoyltransferase, secreted aspartic protease (SAP) and Penicillin-binding protein (PBP3) was performed. From this study, the riparin IV analogue showed interaction energy of -121.0 kcal/mol with 14αlanosterol-dimethylase and of -99.9 kcal/mol with penicillin-binding protein (PBP3), riparin IV, II, III, norRiparinaIII and riparin I showed better interaction energy with exobeta-(1.3)-glucanase, which was possible to suggest that these enzymes are potential antimicrobial targets for such substances.